Subjective Cognitive Decline May Be a Stronger Predictor of Incident Dementia in Women than in Men. - Heser, Kathrin; Kleineidam, Luca; Wiese, Birgitt; Oey, Anke; Roehr, Susanne; Pabst, Alexander; Kaduszkiewicz, Hanna; van den Bussche, Hendrik; Brettschneider, Christian; König, Hans-Helmut; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2019)
BACKGROUND/OBJECTIVE: Subjective cognitive decline (SCD) has often been associated with an increased risk for subsequent dementia. However, sex-specific associations are understudied until now. METHODS: Cross-sectional and longitudinal associations over a follow-up period of up to 13 years were investigated in a sample of participants without objective cognitive impairment at baseline (n = 2,422, mean age = 79.63 years). Logistic regression and Cox proportional hazards models were conducted. RESULTS: Women less frequently reported SCD without worries (p <  0.001), but tended to report more often SCD with worries (p = 0.082) at baseline compared to men. In models adjusted for age, education, cognitive status, and depressive symptoms, SCD at baseline increased the risk for subsequent dementia (p <  0.001), and this effect was less pronounced in males (interaction sex×SCD: p = 0.022). Stratified analyses showed that SCD increased the risk for subsequent dementia in women (HR = 1.77, p <  0.001), but not in men (HR = 1.07, p = 0.682). Similar results were found in analyses with SCD without and with worries, except that SCD with worries also predicted subsequent Alzheimer's disease (AD) in men (p = 0.037). CONCLUSION: At baseline, men reported more SCD without worries and women tended to report more SCD with worries. SCD in women was more strongly associated with subsequent dementia. SCD without and with worries was related to incident dementia and AD in women, whereas in men only SCD with worries increased the risk for AD, but not for all-cause dementia.

Differential Risk of Incident Alzheimer's Disease Dementia in Stable Versus Unstable Patterns of Subjective Cognitive Decline. - Wolfsgruber, Steffen; Kleineidam, Luca; Wagner, Michael; Mösch, Edelgard; Bickel, Horst; Lϋhmann, Dagmar; Ernst, Annette; Wiese, Birgitt; Steinmann, Susanne; König, Hans-Helmut; Brettschneider, Christian; Luck, Tobias; et al. (J Alzheimers Dis, 2016)
BACKGROUND: It is unknown whether longitudinal stability versus instability in subjective cognitive decline (SCD) is a modifying factor of the association between SCD and risk of incident Alzheimer's disease (AD) dementia. OBJECTIVE: We tested the modifying role of temporal stability of the SCD report on AD dementia risk in cognitively normal elderly individuals. METHODS: We analyzed data of 1,990 cognitively normal participants from the longitudinal AgeCoDe Study. We assessed SCD with/without associated worries both at baseline and first follow-up 18 months later. Participants were then classified either as (a) Controls (CO, with no SCD at both baseline and follow-up 1, n = 613), (b) inconsistent SCD (with SCD reported only at baseline or at follow-up 1, n = 637), (c) consistent SCD but without/or with inconsistent worries (n = 610) or (d) consistent SCD with worries (n = 130). We estimated incident AD dementia risk over up to 6 years for each group with Cox-Proportional Hazard Regression analyses adjusted for age, gender, education, ApoE4 status, and depression. RESULTS: Compared to CO, inconsistent SCD was not associated with increased risk of incident AD dementia. In contrast, risk was doubled in the group of consistent SCD without/ with inconsistent worries, and almost 4-fold in the group of consistent SCD with worries. These results could be replicated when using follow-up 1 to follow-up 2 response patterns for group definition. CONCLUSION: These findings suggest that longitudinal stability versus instability is an important modifying factor of the association between SCD and AD dementia risk. Worrisome SCD that is also consistently reported over time is associated with greatly increased risk of AD dementia.

Late-Life Depressive Symptoms and Lifetime History of Major Depression: Cognitive Deficits are Largely Due to Incipient Dementia rather than Depression. - Heser, Kathrin; Bleckwenn, Markus; Wiese, Birgitt; Mamone, Silke; Riedel-Heller, Steffi G; Stein, Janine; Lühmann, Dagmar; Posselt, Tina; Fuchs, Angela; Pentzek, Michael; Weyerer, Siegfried; Werle, Jochen; et al. (J Alzheimers Dis, 2016)
BACKGROUND: Late-life depression is frequently accompanied by cognitive impairments. OBJECTIVE: Whether these impairments indicate a prodromal state of dementia, or are a symptomatic expression of depression per se is not well-studied. METHODS: In a cohort of very old initially non-demented primary care patients (n = 2,709, mean age = 81.1 y), cognitive performance was compared between groups of participants with or without elevated depressive symptoms and with or without subsequent dementia using ANCOVA (adjusted for age, sex, and education). Logistic regression analyses were computed to predict subsequent dementia over up to six years of follow-up. The same analytical approach was performed for lifetime major depression. RESULTS: Participants with elevated depressive symptoms without subsequent dementia showed only small to medium cognitive deficits. In contrast, participants with depressive symptoms with subsequent dementia showed medium to very large cognitive deficits. In adjusted logistic regression models, learning and memory deficits predicted the risk for subsequent dementia in participants with depressive symptoms. Participants with a lifetime history of major depression without subsequent dementia showed no cognitive deficits. However, in adjusted logistic regression models, learning and orientation deficits predicted the risk for subsequent dementia also in participants with lifetime major depression. CONCLUSION: Marked cognitive impairments in old age depression should not be dismissed as "depressive pseudodementia", but require clinical attention as a possible sign of incipient dementia. Non-depressed elderly with a lifetime history of major depression, who remained free of dementia during follow-up, had largely normal cognitive performance.